Unusual Size of Soft Palate Lymphangioma: A Case Report - Wadood, Sundus Abdul; Al-Diab, Jasim Mohammad Ali (Scientific Journal of Medical Research, 2019)
Twenty-two years old female presented with a huge lymphangioma situated in the soft and hard palate crossing the midline and spread out to the left retromolar area. Lymphangioma clinically observed as transparent, smooth, nodular elevations, with reddish to dark purple lymphatic vessels filled by blood. The chief complaint of the patient is bleeding especially with feeding. A biopsy took from the soft palate; histopathological result revealed lymphangioma. The patient treated by intralesional injection of cortisone mixed with dental local anaesthetic contains a vasoconstrictor. The lesion disappeared, and there was no relapse for two years followed up.